British University CFL Teachers’ Practice and Beliefs in Teaching Chinese Characters - Liao, Jiahong (2023)
In the field of teaching Chinese as a Foreign language (TCFL), teachers still have controversial beliefs, such as the role of characters in Chinese foreign language (CFL) learning, and varied practices, such as the methods and approaches in Chinese character teaching (CCT). This study used a mixed methods research design to explore in-service British university Chinese Foreign Language (CFL) teachers’ contextualised CCT practices and beliefs, as well as changes in these. The research questions guiding the study were: 1) How do CFL teachers teach Chinese characters? 2) What beliefs do they have about CCTL? 3) How have their CCT practices and beliefs changed under the influence of cross-cultural teaching? In the quantitative element of the study, 50 British university CFL teachers, including one non-native CFL teacher, while the others all being native Chinese-speaking CFL teachers, were surveyed using a self-designed CCTL beliefs questionnaire constructed from a conceptual framework derived from a thorough review of the literature regarding teachers’ beliefs and pedagogical content knowledge (PCK). In the qualitative element of the study, seven of these teachers were interviewed to discover their beliefs and practices and how these had changed. The study’s findings, for the first time in this field, captured the teacher group’s skill-building-oriented CCT beliefs and revealed the in-service teachers’ systematic CCT practices, including their pedagogical decisions on the three controversial CCT approaches (whether to delay CCT, whether to separate character recognition and writing, and whether to allow typing in place of character writing) and identified 12 CCT strategies; and recognised the seven beliefs underpinning these CCT practices. It also found that the teachers tended to increase their CCT practice in class and that their CCT beliefs tended to become more learner-centred under the influence of their cross-cultural teaching experience. These findings result in an original model describing teachers’ contextualised CCT PCK for the first time in the field, the identification of three CCT orientations, and the discussion of the potential cultural disconnections between L1 Chinese teachers and their local learners in the British context. Such new understandings will contribute much-needed evidence to help improve the development of CCT pedagogy and better prepare future CFL teachers with sufficient cross-cultural teaching awareness in the field of TCFL. Keywords: Teacher beliefs; Pedagogical content knowledge; Chinese character teaching; TCFL; British universities